Impact on the deuterium retention of simultaneous exposure of tungsten to a steady state plasma and transient heat cycling loads. (21st January 2016) - Huber, A; Sergienko, G; Wirtz, M; Steudel, I; Arakcheev, A; Brezinsek, S; Burdakov, A; Dittmar, T; Esser, H G; Kreter, A; Linke, J; Linsmeier, Ch; et al.
Abstract: The impact on the deuterium retention of simultaneous exposure of tungsten to a steady-state plasma and transient cyclic heat loads has been studied in the linear PSI-2 facility with the main objective of qualifying tungsten (W) as plasma-facing material. The transient heat loads were applied by a high-energy laser, a Nd:YAG laser ( λ  = 1064 nm) with an energy per pulse of up to 32 J and a duration of 1 ms. A pronounced increase in the D retention by a factor of 13 has been observed during the simultaneous transient heat loads and plasma exposure. These data indicate that the hydrogen clustering is enhanced by the thermal shock exposures, as seen on the increased blister size due to mobilization and thermal production of defects during transients. In addition, the significant increase of the D retention during the simultaneous loads could be explained by an increased diffusion of D atoms into the W material due to strong temperature gradients during the laser pulse exposure and to an increased mobility of D atoms along the shock-induced cracks. Only 24% of the retained deuterium is located inside the near-surface layer ( d <4 μ m). Enhanced blister formation has been observed under combined loading conditions at power densities close to the threshold for damaging. Blisters are not mainly responsible for the pronounced increase of the D retention.